The Alienation on People with Physical Disability at Bina Daksa Vocational Rehabilitation Centre Cibinong (Global Journal of Human-Social Science, 2019)
This research discussed the alienation of people with disability in Bina Daksa Vocational Rehabilitation Centre (BBRVBD) Cibinong. The alienation refers to the form of experience when people feel themselves as strangers where they do not consider themselves as the centre of the world and the actor of the one's action. This alienation involved the human relation with their lives and environment. The aim of the research was to analyze the alienation of people with disability by observing their powerlessness, normlessness and social isolation. This research used the qualitative method with in-depth interview, observation and documentation study. The data resource which is used was the primary and secondary data, this research also carried out the validity data test with credibility, transferability, dependability and confirmability. The informant in this research was the client of BBRVBD Cibinong which is purposively determined. Furthermore, the field data was analyzed by using qualitative analysis. The result of the research showed that the three informants of this research experienced alienation which is characterized by powerlessness, normlessness, and isolated, live alone and self-estrangement.
Keywords: alienation; people with disability